Biopolymer based photocatalysts and their applications - Badiei M.; Asim N.; Mohammad M.; Akhtaruzzaman M.; Amin N.; Alghoul M.A. (Nova Science Publishers, Inc., 2023)
Photocatalysis is an innovative practical technique which has been widely used to overcome environmental challenges. Photocatalysts are chemically activated upon exposure to ultraviolet irradiation that causes degradation and even demineralization of pollutants. So far, studies have been focused on titanium dioxide (TiO2) as semiconductor photocatalyst. Experimental researches have been directed toward the development of TiO2-based photocatalysts with proper choice of immobilization support to prepare bifunctional adsorbent-photocatalyst composites with industrial photo-oxidation performance. The natural biopolymers have a special affinity for metal and metal oxides. They are new biomatrix for semiconductor photocatalysts that are appropriate for wastewater treatment. This review consists of three main sections. Initially, the necessity of immobilization of photocatalytic nanoparticles is explained. Then, the main structural characteristics of chitosan, alginate and cellulose as adsorbent and templating support are explained. The third section of this chapter summarizes the potential applications of biopolymer-based photocatalysts composites. 2019 by Nova Science Publishers, Inc. All rights reserved. All rights reserved.